Aquisição e desenvolvimento da língua estrangeira (inglês) a partir da teoria noticing hypothesis de Richard Schmidt - ROCHA, Juliane Silva Giusti da (UNIFAP – Universidade Federal do Amapá, 2022)
The study this article aims to investigate the relationship between the capacity of working memory, cognitive record (noticing), care and oral production of LE in a Brazilian adult learners of English as a second or foreign language. This article aims to discuss the Noticing Hypothesis theory proposed by Schmidt (1990) in which it proposed that learners of a foreign language need to note and cognitively record the linguistic aspects of a given new language for learning to occur. The study consisted of three tasks: (1) a task order to measure working memory capacity by Oxford Placement Test; (2) an oral task aiming to measure the oral production of learners LE to produce the target structure (indirect questions); and (3) an assignment which sought to measure the cognitive aspects of registration LE via an oral protocol. The results of this study show that there is a relationship between the memory capacity for work, noticing and oral production of LE, since the learner that has the largest working memory capacity, you can easily record the aspects of the target structure and displays better running in the oral task LE. In other words, the learner with a higher score more linguistic aspects of working memory capacity of the target structure and presents a more accurate performance on oral tasks in LE than a learner with lower working memory capacity that score less formal aspects in LE and demonstrates worse performance on oral tasks of the target structure. Thus, the results of this study show that the learner noticed the target structure because he had a long working memory capacity to store the information obtained. Finally, this article aims to contribute significantly in the field of Applied Linguistics to the theory Acquisition / LE Learning.